Perbedaan Hasil Kadar Hemoglobin Metode POCT Pada Posisi Duduk Dan Berbaring - Sukowati, Ambar; Sukarya, I Gede Andika; Saputri, Maulida Julia (STIKes Medistra Indonesia, 2024)
Hemoglobin is a complex protein that binds to the iron contained in erythrocytes, with its main function being to transport oxygen from the lungs throughout the body and exchange it with carbon dioxide from the tissues to be excreted through the lungs. In outpatient hospitals, blood samples are taken in a sitting position, while inpatients, blood samples are usually taken in a lying position. The purpose of this study was to determine differences in hemoglobin levels by taking capillary blood in the sitting and lying positions, measuring hemoglobin levels using the POCT tool and differentiating hemoglobin levels. This type of research is true experiment research with posttest only control design. The sampling technique used was random sampling, namely 20 respondents from the Poltekkes Kemenkes East Kalimantan. The location of research was carried out at the Hematology Laboratory of the Diploma 3 Technology Laboratory Medical Laboratory of the East Kalimantan Ministry of Health Polytechnic for 2 weeks in June. Data analysis using the bivariate test which was analyzed by paired t-test found that the value of Sig. (2-tailed) of 0.842 > 0.05. From these results it can be concluded that there is no significant difference in the results of hemoglobin levels using the POCT method in sitting and lying positions, so that examination of hemoglobin levels using capillary blood using the POCT method in sitting and lying positions can be used.